Pengaruh Air Limbah Kota Palangka Raya Pada Kualitas Air Sungai Kahayan - Leonardo Leonardo; Rosana Elvince; Ardianor Ardianor (Journal of Environment and Management, 2020)
Rivers are environmentally vulnerable to pollution, mainly due to domestic activities. The water quality of the Kahayan River in Palangka Raya city is currently threatened by domestic waste that has not been improperly taken. This study aims, first, to assess whether the quality of wastewater in the Kahayan river meets the specified wastewater quality standards. Second, to determine the effect of wastewater on the Kahayan River in Palangka Raya City. The quality of wastewater and the quality of the Kahayan River water were tested using the parameters of pH, BOD, COD, TSS, OilFat, Ammonia and Total Coliform. The results are, then, compared with applicable quality standards, and analysed using a statistical approach. As the results, the BOD, TSS, Oil-Fat and Coliform parameters have exceeded the domestic wastewater quality threshold. Consequently, the wastewater should not be released into the river. Besides, the wastewater has not been significantly affecting river water property, except for the COD parameter at morning measurement time.